Pyrolysis Kinetics of Spirulina platensis and Non-condensable Gas Product Distribution in a Fixed-Bed Reactor - Aminullah, Ahmad Yusril; Sukarni, Sukarni; Wulandari, Retno; Shahbaz, Muhammad (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Energy is a fundamental factor for civilization development and sustainability. However, energy sources are dominated by non-renewable fractions, such as fossil fuels. Renewable biomass is projected to be a future fuel source. Spirulina platensis (SP) has numerous advantages compared to other biomass, and it is considered 3rd generation biomass that does not interfere with food and land usage and has a relatively low main decomposition temperature at 325.7℃. Thermogravimetric analysis (TGA) was conducted to observe SP kinetics parameters, especially activation energy. Kissinger-Akahira-Sunose (KAS), Ozawa-Flynn-Wall (OFW), and Starink iso-conversional methods reveal that SP has an activation energy of 152.33, 154.56, and 152.78 kJ/mol, respectively. The coefficient correlation (R2) of OFW is the highest compared to its counterpart at 0.9918. Non-condensable gas (H2, CH4, and CO2) product distribution is characterized using a fixed-bed pyrolysis reactor. The average concentrations of H2, CH4, and CO2 are 3775.2, 83792.19, and 23592.58 ppm, in that order. H2 production is linked with carbohydrates and protein decomposition. CH4 yield heavily depends on protein degradation, followed by carbohydrates and lipids. CO2 yield mainly originated from carbohydrate cracking. The optimum SP pyrolysis temperature is 310—370℃ based on its non-condensable gas yield, TGA result, OFW kinetics method, and thermodynamics parameter, where it has relatively low activation energy (139.29 kJ/mol) accompanied by a significant increase of non-condensable-gas-production.